2019
DOI: 10.1111/iej.13142
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the effectiveness of the Dental Practicality Index in predicting the outcome of root canal retreatments

Abstract: Aim To assess the effectiveness of the Dental Practicality Index (DPI) in predicting the outcome of root canal retreatment in posterior teeth. Methodology One hundred and thirty‐seven posterior teeth with symptoms and/or signs of post‐treatment endodontic disease requiring root canal retreatment and previously included in a clinical trial were selected. Clinical and radiographic examinations including digital periapical and cone beam computed tomography (CBCT) were obtained pre‐treatment and 1‐year postoperati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Tifooni et al assessed the effectiveness of the Dental Practicality Index (DPI) in predicting the outcome of root canal retreatment in posterior teeth. 49 The results of the study highlighted that using the index gave a good outcome prediction for root canal retreatments. This shows although restorability indexes can be complex, they can be effective.…”
Section: Materials Choice and Tooth Related Factorsmentioning
confidence: 84%
“…Tifooni et al assessed the effectiveness of the Dental Practicality Index (DPI) in predicting the outcome of root canal retreatment in posterior teeth. 49 The results of the study highlighted that using the index gave a good outcome prediction for root canal retreatments. This shows although restorability indexes can be complex, they can be effective.…”
Section: Materials Choice and Tooth Related Factorsmentioning
confidence: 84%
“…37 The description of the amount of remaining tooth structure varied across the studies. Hence, a recognized index (Dental Practicality Index or DPI) 31,47 was used to standardise the manner in which the residual tooth structure was classified. The amount of tooth structure in all the included studies conformed to Level 2 structural integrity of DPI.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study found that utilising the DPI gave a good prediction for the outcome of endodontic retreatments although further validation is required. 38 Although not specifically an aid for SDM, this would help dentists to be able to decide predictably what treatment options need to be offered to the patient, thereby reducing the variations in clinical decision making. In a similar way, when the clinician has an up to date awareness of what the evidence base tells us about treatment outcomes, this will also support SDM.…”
Section: Minimising Uncertainty In the Clinical Settingmentioning
confidence: 99%